Promotion of high capacity broadband to rebuild and recover from the pandemic - J. Scott Marcus; Alicia García Herrero; Lionel Guetta-Jeanrenaud (Bruegel, 2022)
Promoting high-quality fixed and mobile broadband for all, at an affordable price, is an important enabler of the digital transformation of society and will help close the digital divide. This became clearer than ever during the pandemic, when broadband access was a crucial enabler of remote work, distance learning, telemedicine and e-commerce. It has always been challenging to provide broadband access to all at an affordable price. The pandemic, global geopolitical tension and Russia's invasion of Ukraine have exacerbated supply-chain disruptions in ways that make this even more difficult and potentially expensive. Promotion of broadband deployment, adoption and use are all important for both fixed and mobile broadband; however, different policy levers are needed in each case, on both the supply and demand sides. The market will not always deliver complete solutions. Consequently, there is a role for regulation, targeted industrial policy and public finance. Promotion of competition, combined with prompt and efficient provision of access to resources such as electromagnetic spectrum and access to land and rights of way, can be particularly important. G20 countries and others now seek a future-proof, sustainable and equitable recovery, meaning new sources of public revenues need to be considered. Broadband can be boosted by judicious use of recovery funds and expected new tax revenues arising from global tax reforms agreed within the Organisation for Economic Co-operation and Development.
Keywords: 330